Stressors in midlife and risk of dementia: The role of race and education - Gilsanz, Paola (Alzheimer Dis Assoc Disord, 2019)
BACKGROUND: Post-traumatic stress disorder is associated with increased dementia risk but less is known about stress due to everyday problems in diverse populations. METHODS: 9,605 healthcare plan members who provided information regarding midlife stressors in 1972–1973 (ages 40–55) were followed for dementia diagnosis between 1996–2017. Cox proportional hazard models evaluated associations between midlife stressors and dementia adjusting for demographics and lifecourse health indicators. RESULTS: ≥1 midlife stressor was associated with 17% greater dementia risk (HR=1.15, 95%CI:1.07–1.27) versus 0 midlife stressors and 26% increased risk among those with ≤high school education (HR=1.26, 95% CI:1.09–1.44) adjusting for demographics. Compared to Whites without stressors, Whites with ≥1 stressor had 13% greater dementia risk (HR=1.13; 95% CI:1.02–1.24), Blacks without stressors 19% greater risk (HR=1.19; 95% CI:1.08–1.32), and Blacks with ≥1 stressors 47% greater risk (HR=1.47; 95% CI:1.27–1.69) in fully-adjusted models. Resource problems were associated with 20% greater risk (HR=1.20; 95% CI:1.01–1.42) than interpersonal problems. CONCLUSION: Reporting ≥1 serious midlife stressor was associated with elevated dementia risk, especially stressors related to resources problems and for those with ≤high school education. Everyday stressors can impact brain health over the long-term and may contribute to racial inequities in dementia rates, though education can be a mitigating factor.